Elite configurations at the apex of power / edited by Mattei Dogan. - Dogan, Mattei (International studies in sociology and social anthropology, 2003)
This text focuses on the interpenetration between various types of elites: politicians, owners of capital, corporate managers, higher state administrators, directors of public enterprises, controllers of media, military officers and the civic-cultural establishment.